Individual and combined heat and UV-C radiation hurdles against Escherichia coli O157 H7, Salmonella enterica, and listeria monocytogenes in orange juice - Pagal, Gladess A. (College of Home Economics, University of the Philippines Diliman, 2019)
Abstract